Pengelolaan Desa Wisata Berbasis Masyarakat sebagai Penguatan Ketahanan Pangan - Danang Prasetyo; Viona Amelia (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The availability of food supplies as a form of readiness to meet the needs of the population is critical to avoid prolonged political and social turmoil. In situations like this, Indonesia can take a role in efforts to build a sustainable food system that is resilient to future shocks and contribute to achieving the second goal of SDGs 2030, namely zero hunger. National food security is predicted to be more guaranteed through the tourism sector. This study aims to identify the role of rural tourism as a key actor in realizing sustainable development through food security. The method used in this study is a literature review, namely a study of research articles on the subject of strengthening food security through rural tourism. The results showed that several Indonesian tourist villages were provided with assistance in maximizing land management so that it would be beneficial for maintaining the stability of household-scale food security. Tourism villages as owners of agricultural and fishery land assets have enormous power to introduce local food resources to visitors and tourists. Tourism villages also have a crucial role as actors in maintaining and succeeding in the success of global food security.